The Role of the Mentor in Medical education: History, evolution, and current challenges - Perez-Martinot, Manuel (2024)
Mentoring in medical education has been fundamental since ancient times. It facilitates the transmission of scientific and technical knowledge and the development of competencies like empathy and leadership. In contemporary medicine, signaled by technological advances and specialization, mentors are crucial to maintaining the integrity and humanization of medical practice, positively influencing professionals' ethical and clinical conduct. This article explores the history and evolution of mentoring, including its current challenges, like time limitations, lack of resources, and pressure for performance that may affect effective relationships. We reinforce the need to implement structured programs and adequate training for mentors to overcome the identified challenges to ensure effective mentoring, thus preparing future professionals in technical, ethical, and humanistic abilities.